2020
DOI: 10.3390/ph13010011
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Chitosan–Polyanion Nanoparticles by Polyelectrolyte Complexation Assisted by High-Intensity Sonication for the Modified Release of Methotrexate

Abstract: A promising strategy to improve the effectivity of anticancer treatment and decrease its side effects is to modulate drug release by using nanoparticulates (NPs) as carriers. In this study, methotrexate-loaded chitosan–polyanion nanoparticles were produced by polyelectrolyte complexation assisted by high-intensity sonication, using several anionic polymers, such as the sodium and potassium salts of poly(maleic acid-alt-ethylene) and poly(maleic acid-alt-octadecene), here named PAM-2 and PAM-18, respectively. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 61 publications
2
11
0
Order By: Relevance
“…Particle sizes around 400 nm and 1 µm were evidenced for P(3HB-3HV)-CS-Neo and P(3HB-3HV)-CS-Kan systems, respectively. The obtaining of nano-/micro-aggregates was previously reported for CS [ 68 , 69 ] and polyester/CS [ 70 , 71 ], as higher concentrations of CS are related with increased hydrogen bonds between CS molecules and electrostatic interactions with organic salts.…”
Section: Resultsmentioning
confidence: 69%
“…Particle sizes around 400 nm and 1 µm were evidenced for P(3HB-3HV)-CS-Neo and P(3HB-3HV)-CS-Kan systems, respectively. The obtaining of nano-/micro-aggregates was previously reported for CS [ 68 , 69 ] and polyester/CS [ 70 , 71 ], as higher concentrations of CS are related with increased hydrogen bonds between CS molecules and electrostatic interactions with organic salts.…”
Section: Resultsmentioning
confidence: 69%
“…The mathematical models applied to represent the release mechanisms of the active drug from the formulation were zero-, first-, second-order as well as Higuchi, Korsmeyer–Peppas and Hixon–Crowell models yielded R values of 0.59, 0.47, 0.33, 0.40, 0.90 and 0.51, respectively. The optimized formulation displayed a good fit to the Korsmeyer–Peppas ( R = 0.90 ) and the computed n-value was 0.83, meaning that drug release after formulation hydration was controlled by an anomalous drug diffusion process followed by matrix relaxation (disentangling polymer chains or disintegration) and erosion (matrix dissolution) [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The slight shift of the PZA peak in the mixture may have been influenced by polymeric crystallization occurring during the formation of the orodispersible formulation resulting in the endothermic peak slightly shifting to 193 °C , accounting as the Tm of the newly prepared drug loaded formulation further confirming drug stability within the The mathematical models applied to represent the release mechanisms of the active drug from the formulation were zero-, first-, second-order as well as Higuchi, Korsmeyer-Peppas and Hixon-Crowell models yielded R values of 0.59, 0.47, 0.33, 0.40, 0.90 and 0.51, respectively. The optimized formulation displayed a good fit to the Korsmeyer-Peppas (R = 0.90) and the computed n-value was 0.83, meaning that drug release after formulation hydration was controlled by an anomalous drug diffusion process followed by matrix relaxation (disentangling polymer chains or disintegration) and erosion (matrix dissolution) [45].…”
Section: Optimized Formulation Characterizationmentioning
confidence: 87%
“…It had been found that the drug release pattern obeyed Korsmeyer model. Korsmeyer et al, (1983) derived a simple relationship which described the drug release from a polymeric system 21 , Ritger and Peppas 22 , and Korsmeyer and Peppas 23 developed an empirical equation to analyze both Fickian and non-Fickian release of drug from swelling as well as non-swelling polymeric delivery systems.…”
Section: Fig 8: Cumulative Percent Of Drug Released From Superporousmentioning
confidence: 99%